A Case of Warm Autoimmune Hemolytic Anemia and a Pulmonary Embolus in a Patient Treated with Triple Therapy - Gurchetan Randhawa; Chia-Yu Chiu; Thanunthorn Suban Na Ayutthaya (Case Reports in Hematology)
Autoimmune hemolytic anemia (AIHA) can be caused by a variety of etiologies. AIHA is associated with the development of coagulopathy, leading to potentially fatal pulmonary emboli. Here, we present a case of a 66-year-old female with a past medical history of non-Hodgkin’s lymphoma and gastritis treated with triple therapy that developed warm AIHA. The patient later succumbed to a suspected pulmonary embolus.